ADAPTIVE STABILITY MODEL FOR CONTROLLING INFLATION AND UNEMPLOYMENT UNDER COVID-19 WITH LOW UNEMPLOYMENT IN 6 ADJUNCT COUNTRIES (USA, JAPAN, ICELAND, THAILAND, INDONESIA, BELARUS) - Rike Aulia; Rusiadi, Rusiadi; Bakhtiar Efendi (PT. Arsil Reka Engineering, 2024)
This study aims to analyze the optimalization of monetary policy and fiscal policy (current policies) in stabilizing the economy, to be precise in overcoming the unemployment rate during the pandemic in the 6 world’s highest unemployment countries (South Africa, Colombia, Philippines, Brazil, Chile, and United States). Where the monetary variables (Total Money Supply and Real Interest Rates), fiscal policy (government expenture and TAX revenue), and economic stability (inflation, GDP, and wages). This study uses secondary data or time series from 2005 to 2019. The data analysis models in this study are Simultaneous Regression, Vector Autogression (VAR) model, and ARDL Panel seen from sharpening with Impulse Response Function (IRF) analysis, and Forecast Error Variance Decomposition (FEVD), and ARDL Panel. The results of the IRF analysis show that the stability of the variable response is formed in period 8 or medium term and period 15 or long term, where the response of other variables to changes in one variable shows different variations from positive to negative responses or vice versa, and there are variables whose responses remain positive. to negative from short to long term. FEVD analysis results show a leading indicator as an operational target. Then the results of the ARDL Panel analysis show that the Inflation Panel, Total Money Supply, Interest Rates, Gross Domestic Product, Government Expenditure, TAX Revenue, and Wages are able to control economic stability, precisely at the unemployment rate in the 6 in the world’s highest unemployment countries back in the short term, as well as long-term.